DEVELOPMENT OF SUSTAINABILITY-ORIENTED MICRO ENTERPRISES IN THE LIKUPANG NATIONAL SUPER PRIORITY ZONE - Asngadi, Asngadi; Sutomo, Maskuri; Haryanti, Tuti; Latifah, Ayi; Krisnamurti, Reza Mahendra (Universitas Tadulako, 2024)
The area-based workforce development initiative is a premier program of the Ministry of Manpower aimed at generating new employment opportunities through independent entrepreneurship across several regions, including the Likupang National Super Priority Area. This study aimed to assess the effects of the micro, small and medium-sized enterprises (MSMEs) program's implementation in the Likupang national super priority area. Data gathering for the research was conducted via observation, questionnaires, focus group discussions, and in-depth interviews with company participants who had received support and coaching from the Ministry of Manpower. The study's results indicated that not all program enrollees were able to develop. The economic impact of certain MSMEs developments was shown in the rise in sales turnover, enhanced capacities, and the strengthening of market networks. The support of ecosystems and the facilitation of local government would further expedite the development of MSMEs in the Likupang national super priority region. MSMEs initiatives in horticulture, plastic waste processing, and agricultural waste processing demonstrate its commitment to sustainability in the Likupang national super priority region.